2011
DOI: 10.1097/mjt.0b013e3181cea0ef
|View full text |Cite
|
Sign up to set email alerts
|

Acute Dyspnea From Treatment of AL Amyloidisis With Bortezomib

Abstract: Bortezomib with or without dexamethasone has been reported to be very effective and well tolerated in the treatment of AL amyloidosis. Commonly reported adverse effects are fatigue, nausea, vomiting, diarrhea, constipation, postural hypotension from autonomic neuropathy, peripheral neuropathy, thrombocytopenia and anemia. Dyspnea has been rarely reported as an adverse effect of bortezomib therapy in AL amyloidosis. We are reporting three case reports of patients suffering from AL amyloidodis, who had new onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Pulmonary arterial hypertension is a known complication of dasatinib and is commonly seen after 8 to 48 months of treatment [ 21 24 ]. Although less common, pulmonary arterial hypertension has been reported with bortezomib as well [ 25 , 26 ]. It was unclear if dasatinib was the only culprit in our patient's pulmonary hypertension as he also sustained a cardiac event and he later admitted to taking an unknown “diet pill” which might have all contributed to developing pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary arterial hypertension is a known complication of dasatinib and is commonly seen after 8 to 48 months of treatment [ 21 24 ]. Although less common, pulmonary arterial hypertension has been reported with bortezomib as well [ 25 , 26 ]. It was unclear if dasatinib was the only culprit in our patient's pulmonary hypertension as he also sustained a cardiac event and he later admitted to taking an unknown “diet pill” which might have all contributed to developing pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have indicated that patients suffer from cardiomyocytes necrosis along with liver and kidney damage after three months of treatment with BTZ . Patients also suffer from other side effects, such as nausea, vomiting, diarrhea, and even shock . As a commercial drug comprising a chelate of BTZ and mannitol, Velcade could not be transported to tumor tissues effectively.…”
Section: Introductionmentioning
confidence: 99%